Desain Antarmuka Pengguna Sistem Informasi Pengelolaan Penyimpanan Bukti Fisik Penilaian Akreditasi Sekolah Menggunakan Goal Directed Design (Studi Kasus: Sekolah Menengah Pertama Islam Sabilurrosyad Malang) - Vrishi Magridira Putri; Ismiarta Aknuranda; Hanifah Muslimah Az-zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
SMPI Sabilurrosyad Malang is an Islamic high school located in Malang, East Java. According to government regulations, each school is required to conduct accreditation evaluations periodically with a predetermined time. Malang Sabilurrosyad Middle School has problems in preparing documents related to school accreditation. This is because no system helps in the management of documents. Based on these problems in this thesis an information system was designed to assist in the management of school accreditation documents. The system design is done by using a goal directed design approach to produce a user interface that is by user objectives and meets business process requirements. At the end of the design, a usability test was conducted using the think aloud method, which produced qualitative data in the form of input from 5 respondents. Usability testing was also carried out quantitatively using a single ease questionnaire. This questionnaire measures how easy the user is in completing a task on the system that produces a value of 6.83 for respondents Principal and 6.93 for respondents a member of the school development team, this value means the user is very easy to complete tasks on the system that has been designed.